2021
DOI: 10.1186/s43159-021-00078-8
|View full text |Cite
|
Sign up to set email alerts
|

A retroperitoneal supra-adrenal non-communicating gastric duplication cyst: a case report and comprehensive literature review

Abstract: Background Gastric duplication cyst is a rare congenital anomaly. It is usually located in close proximity to the stomach. Nevertheless, there have been seldom reports in the literature that describe unusual locations. Retroperitoneal gastric duplications cysts are extremely rare and are usually confused with renal or adrenal cysts. Case presentation In this case report, we are presenting a 2-year-old girl with a complaint of bouts of abdominal pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Despite all of that, the mimicking of GDCs as an adrenal mass has rarely been reported [3]. Al Awfi et al [3] reported a case of a 2-year-old girl with abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite all of that, the mimicking of GDCs as an adrenal mass has rarely been reported [3]. Al Awfi et al [3] reported a case of a 2-year-old girl with abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all of that, the mimicking of GDCs as an adrenal mass has rarely been reported [3]. Al Awfi et al [3] reported a case of a 2-year-old girl with abdominal pain. The preoperative diagnosis based on imaging suggested a retroperitoneal supra-adrenal cyst.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations